Financial Development and Source of Growth : New Evidence - Ben Naceur, Sami.; Blotevogel, Robert; Fischer, Mark.; Shi, Haiyan (Washington, D.C. : International Monetary Fund, 2017)
This paper examines how financial development affects the sources of growth-productivity and investment-using a sample of 145 countries for the period 1960-2011. We employ a range of econometric approaches, focusing on the CCA and MENA countries. The analysis looks beyond financial depth to capture the access, efficiency, stability, and openness dimensions of financial development. Yet even in this broad interpretation, financial development does not appear to be a magic bullet for economic growth. We cannot confirm earlier findings of an unambiguously positive relationship between financial development, investment, and productivity. The relationship is more complex. The influence of the different dimensions of financial development on the sources of growth varies across income levels and regions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet